2012
DOI: 10.3892/ijo.2012.1746
|View full text |Cite
|
Sign up to set email alerts
|

The tumor suppressor gene RhoBTB1 is a novel target of miR-31 in human colon cancer

Abstract: miRNAs are a class of endogenous non-coding RNA, which can regulate downstream target genes through binding to the 3'UTR of those genes. Numerous studies have indicated that abnormal expression of miRNAs is implicated in tumor development. Aberrant expression of miR-31 has been found in various cancers, including colorectal cancer. Here, we show that miR-31 is upregulated in human colon cancer tissues and cell lines, and that repression of miR-31 inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 39 publications
2
41
0
Order By: Relevance
“…miR-31 is a highly evolutionarily conserved miRNA that plays a role in cancer and bone homeostasis in vertebrates; however, the function of miR-31 has not been well defined in the developing embryo (Aboobaker et al, 2005;Wienholds et al, 2005;Valastyan and Weinberg, 2010;Yamagishi et al, 2012;BaglĂŹo et al, 2013;Deng et al, 2013a,b;Xu et al, 2013). Previously, we identified miR-31 as highly expressed in the early sea urchin embryo, and miR-31 was one of the four miRNAs that was needed to rescue the developmental defects induced by KD of the key miRNA processing enzyme Drosha, indicating the potentially important role of miR-31 in early development (Song et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…miR-31 is a highly evolutionarily conserved miRNA that plays a role in cancer and bone homeostasis in vertebrates; however, the function of miR-31 has not been well defined in the developing embryo (Aboobaker et al, 2005;Wienholds et al, 2005;Valastyan and Weinberg, 2010;Yamagishi et al, 2012;BaglĂŹo et al, 2013;Deng et al, 2013a,b;Xu et al, 2013). Previously, we identified miR-31 as highly expressed in the early sea urchin embryo, and miR-31 was one of the four miRNAs that was needed to rescue the developmental defects induced by KD of the key miRNA processing enzyme Drosha, indicating the potentially important role of miR-31 in early development (Song et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the work on miRNAs has been done in cancer models, showing how the regulation of Rho GTPase expression by miRNAs can affect cancer progression. 49 For example, it has been shown that RhoA is target of miRNA-155 50,51 and miRNA-125a-3p; 52 RhoB is a target of miRNA- 21; 53 RhoBTB1 is a target of miRNA-31; 54 and Cdc42 is a target of miRNA-29 55 and miRNA-137. 56 Sometimes the same miRNA can target 2 different Rho GTPases.…”
Section: 43mentioning
confidence: 99%
“…122 The RhoBTB2 gene has been shown to be a target of E2F1, a transcription factor involved in cell cycle and apoptosis 126 and RhoBTB1 is a target of microRNA-31 (miR-31) in human colon cancer. 54 These examples illustrate how complex the role of Rho GTPases in tumor progression is. Their contributions are dependent on cell type, extracellular stimuli and signaling pathways involved in the particular cancer type or cancer cell line.…”
mentioning
confidence: 99%
“…The gene is also expressed in foetal tissues (Ramos et al, 2002;Nagase et al, 1998). Expression of RHOBTB1 has been found decreased in kidney, breast and stomach tumors in a cancer profiling array (Berthold et al, 2008), in 37% of 46 head and neck squamous cell carcinomas (Beder et al, 2006) and in colon cancer tissues (Xu et al, 2013). RHOBTB1 is a target of the microRNA MIR31- (Alder et al, 2012;Xu et al, 2013).…”
Section: Expressionmentioning
confidence: 99%
“…Downregulation of RHOBTB1 is responsible for the tumor promoting effects of miR-31. Silencing of RHOBTB1 in the colon cancer cell line HT29 increases cell proliferation and promotes cell clonal growth, mimicking the effects of increased miR-31 expression (Xu et al, 2013).…”
Section: Colon Cancermentioning
confidence: 99%